Studi Literatur: Teknik Audit Investigatif Dalam Pengungkapan Money Laundering Dari Perspektif Akuntan Forensik - Immanuel Calvin Fernaldi; Tri Ratnawati (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Forensic accounting and investigative auditing are disciplines used when investigating complex cases of fraud related to the law. It contains investigative audit techniques that can help forensic accountants in their implementation. In Indonesia, investigative audits are more often associated with solving corruption cases, one of which is money laundering. So in this research the author wants to find out what investigative audit techniques are most effective in uncovering money laundering cases based on the perspective of forensic accountants. The research method used is a qualitative descriptive method. Based on the results of the analysis, the results of the investigative audit stages were predication, hypothesis formulation, data gathering, data reliability testing, data analysis, calling for interviews and interrogation, loss calculation, and reporting. Then it was also concluded that in theory and practice no investigative audit technique was chosen as the most effective technique. Because beforehand forensic accountants need to consider the matters and characteristics of money laundering cases, only then determine which investigative audit techniques will be used.